THE FUNCTION OF MOTIVATION IN IMPROVING THE WORK SPIRIT OF THE STATE CIVIL APPARATUS IN THE KASINTUWU LURAH OFFICE, POSO DISTRICT, UTARA KOTA, POSO REGENCY - Suwardhi Pantih; Sartika Andi Patau; Herlanlagantondo (Media Inovasi Pendidikan dan Publikasi, 2023)
The function of motivation in increasing the morale of the State Civil Apparatus at the Kasintuwu Village Head Office, Poso District, North City, Poso Regency. The purpose of the study was to determine the implementation of motivation in increasing the morale of the State Civil Apparatus at the Kasintuwu Village Head Office, Poso District, North City, Poso Regency. The method used is a survey with a descriptive research type. Data collection techniques through observation, interviews and documentation. The results of this study indicate that the motivation to increase the morale of the State Civil Apparatus at the Kasintuwu Village Head Office, Poso District, North City, Poso Regency is very influential. It is evident from the results of the study that the respondents gave very influential answers and the factors that influence motivation are human resources, facilities and infrastructure as well as employee placement.